Radiopharmaceuticals for Relapsed or Refractory Leukemias - Kunos, Charles A.; Capala, Jacek; Ivy, Susan Percy (Frontiers in Oncology, 2019)
Radiopharmaceuticals, meaning drugs that hold a radionuclide intended for use in cancer patients for treatment of their disease or for palliation of their disease-related symptoms, have gained new interest for clinical development in adult patients with relapsed or refractory leukemia. About one-third of adult patients outlive their leukemia, with the remainder unable to attain complete remission status following the first phase of treatment due to refractory bone marrow or blood residual microscopic disease. The National Cancer Institute (NCI) Cancer Therapy Evaluation Program conducted 49 phase 1-1b trials in adult patients with leukemia between 1986 and 2017 in an effort to discover tolerated and effective therapeutic drug combinations intended to improve remission and mortality rates. None of these trials involved radiopharmaceuticals. In this article, the NCI perspective on the challenges encountered in and on the future potential of radiopharmaceuticals alone or in combination for adult patients with relapsed or refractory leukemia is discussed. An effort is underway already to build-up the NCI’s clinical trial enterprise infrastructure for radiopharmaceutical clinical development.